Comparative efficacy and safety of acupoint injection-related therapies for the treatment of intractable hiccup after stroke: a network meta-analysis - Tan, Jun; Xu, Ruihua; Lin, Lixue; Luo, Mengqing; Ge, Jialei; Liu, Jiabao; Ma, Yan; Su, Wen; Sun, Rui (Frontiers in Neurology, 2026)
ObjectiveTo systematically evaluate the effectiveness of various therapies (acupoint injection, acupuncture, etc.) in alleviating intractable hiccups after stroke through a comprehensive systematic review and network meta-analysis.MethodsWe searched multiple databases up to July 2025 to find clinical randomized controlled trials on acupoint injection-related therapies for post-stroke intractable hiccups. Three authors independently screened studies. The quality of included studies was assessed according to PRISMA guidelines using the Cochrane RoB2 tool. Traditional meta-analyses of binary outcomes were performed with a fixed-effects model in Stata 17.0, complemented by prespecified subgroup analyses; comparative efficacy across interventions was subsequently estimated via network meta-analysis.ResultsTwenty-one studies with 2,127 participants were included, and 17 studies with 1,658 participants were in the meta-analysis. The 95% confidence interval for the odds ratio of treatment effectiveness was (3.10, 7.63), indicating acupoint injection-related therapies were more effective than non-acupoint injection ones. The NMA of all 21 studies found that the combination of conventional acupuncture with auricular acupuncture exhibited the highest treatment efficacy (SUCRA 86.5%). This was closely followed by acupoint injection integrated with Western medical therapy (SUCRA 85.3%), while the regimen combining acupoint injection with standard acupuncture yielded a more modest efficacy profile (SUCRA 71.9%). However, the evidence quality of many interventions was low. Sensitivity analyses confirmed the findings’ robustness, and no publication bias was detected.ConclusionAcupoint injection-related therapies, particularly the combined application of acupuncture, acupoint injection, auricular therapy, and Western medications, demonstrate significant efficacy in alleviating intractable hiccups after stroke. This approach offers valuable reference and guidance for clinical treatment.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, Identifier CRD42024601310.